Combined Hemorrhagic Shock and Unilateral Common Carotid Occlusion Induces Neurological Injury in Adult Male Rats - Chio, Chung-Ching (Int J Med Sci, 2017)
Background: Clinical assessment reveals that patients after surgery of cardiopulmonary bypass or coronary bypass experience postoperative cognitive dysfunction. This study aimed to investigate whether resuscitation after a hemorrhagic shock (HS) and/or mild cerebral ischemia caused by a unilateral common carotid artery occlusion (UCCAO) can cause brain injury and concomitant neurological dysfunction, and explore the potential mechanisms. Methods: Blood withdrawal (6 mL/100 g body weight) for 60 min through the right jugular vein catheter-induced an HS. Immediately after the termination of HS, we reinfused the initially shed blood volumes to restore and maintain the mean arterial blood pressure (MABP) to the original value during the 30-min resuscitation. A cooling water blanket used to induce whole body cooling for 30 min after the end of resuscitation. Results: An UCCAO caused a slight cerebral ischemia (cerebral blood flow [CBF] 70%) without hypotension (MABP 85 mmHg), systemic inflammation, multiple organs injuries, or neurological injury. An HS caused a moderate cerebral ischemia (52% of the original CBF levels), a moderate hypotension (MABP downed to 22 mmHg), systemic inflammation, and peripheral organs injuries. However, combined an UCCAO and an HS caused a severe cerebral ischemia (18% of the original CBF levels), a moderate hypotension (MABP downed to 17 mmHg), systemic inflammation, peripheral organs damage, and neurological injury, which can be attenuated by whole body cooling. Conclusions: When combined with an HS, an UCCAO is associated with ischemic neuronal injury in the ipsilateral hemisphere of adult rat brain, which can be attenuated by therapeutic hypothermia. A resuscitation from an HS regards as a reperfusion insult which may induce neurological injury in patients with an UCCAO disease.